Fomepizole in the treatment of acute methanol poisonings: experience from the Czech mass methanol outbreak 2012-2013 - Zakharov, Sergey; Navratil, Tomas; Pelclova, Daniela (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2014)
OBJECTIVE: During an outbreak of mass methanol poisonings in the Czech Republic in 2012-2013, fomepizole was applied as an alternative antidote to ethanol. We present the laboratory data, clinical features, adverse reactions, and treatment outcomes in all patients treated with fomepizole. METHODS: Combined retrospective and prospective case series study in 25 patients, median age 50 (16-73) years, 18 males and 7 females. RESULTS: There were 24% fatalities, 36% survivors without health impairment, and 40% survivors with sequelae. All the patients who died were comatose on admission; the mortality was 50% among patients in a coma. The median intensive care unit length of stay was six (2-22) days. The median total dose of fomepizole was 2 (1-9) g. Complications were observed in 7/25 cases: aspiration pneumonia (4), sepsis (2), bleeding (2), malignant arrhythmia (1), delirium tremens (1), and rebound of acidosis (1). The patients who survived without impairment were less acidotic than those who died or survived with sequelae (P<0.01). No difference in serum methanol and formate was found between the three groups. CONCLUSION: There is no evidence whether fomepizole is a more efficient antidote than ethanol with regards to the hospital mortality. The possibility of delirium tremens in the patients with a history of chronic alcohol abuse has to be taken in consideration. The benefits of fomepizole were indirect: no need to monitor serum ethanol's level during the hemodialysis in severely poisoned patients and less working overload on ICU doctors treating several poisoned patients simultaneously.
Keywords: epidemický výskyt choroby; Hospital Mortality; mužské pohlaví; Retrospective Studies; Antidotes; antidota; Male; Czech Republic; výsledek terapie; retrospektivní studie; ethanol; Female; Humans; Ethanol; lidé; fomepizol; Prospective Studies; Middle Aged; ženské pohlaví; lidé středního věku; pyrazoly; Disease Outbreaks; Česká republika; mladiství; Fomepizole; Young Adult; Adolescent; Pyrazoles; Treatment Outcome; methanol; prospektivní studie; mladý dospělý; Methanol; dospělí; Adult; mortalita v nemocnicích